(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
The proposed classification was exclusively on the basis of biosynthetic gene clusters encoding for only antibiotic proteins. Biosynthetic gene clusters (BGCs) are organized groups of genes within the genome of prokaryotes which are involved in the production of specialized bioactive compound. These biosynthetic gene clusters contain all the genes encoding for the production of enzymes that catalysed the formation of antibiotic proteins, these include ribosomal peptides which are synthesized by the ribosome (RP), non-ribosomal peptides synthetase (NRPS).The antibiotic proteins produced by the members of the domain archaea are mainly archaeocins which are synthesized by the ribosomal pathways. Archaea have been overlooked and therefore under investigatigated for antibiotic proteins production, because only 15 achaeocins were described and characterized from haloarchaea and sulfolobus archaea, while there are many potentially untapped archaeocins in the archaeal environment, however, today there is an increase in the number of research on archaea due to the availability of molecular techniques such as 16S ribosomal RNA gene sequencing and metagenomic sequencing which revealed that they are found in not only the extreme environment but also the non-extreme (common) environment. Bacteriocins are protein toxins that inhibit the growth of similar or closely related bacterial strains at a certain concentration.Bacteriocins with their properties such as thermal tolerance and wide pH activity are now becoming promising alternatives to conventional antibiotics. Research into their production, mechanisms of action, and spectrum of activity can position them as valuable and safe antibiotic agents. Expanding research on Archaea and Bacteria using molecular techniques such as next-generation sequencing, CRISPR-Cas9 gene editing and genome mining resources (antiSMASH) can enhance the exploration and discovery of novel antibiotics and their BGCs.